PRE-PLANTING TREATMENTS FOR DESERT AND PASTURE ECOSYSTEMS: A COMPREHENSIVE ANALYSIS (American Journal of Pedagogical and Educational Research, 2023)
This scientific article presents a comprehensive analysis of pre-planting treatments in deserts and pastures, aiming to improve vegetation establishment and growth in challenging environments. The study explores the existing literature, analyzes various pre-planting techniques, assesses their effectiveness, and discusses their implications for desert and pasture ecosystems. The findings provide valuable insights for land managers and researchers to optimize pre-planting strategies and contribute to sustainable ecosystem restoration and management.